Cancelled: Effect of Cyber-Ostracism on the Mental Condition of Instagram Users - Cleoputri Yusainy; Intan Liana Putri; Lita Rakhmi Fadliilah; Gracia Maria Veronica; Ircham Darmawan; Wahyu Wicaksono (Psympathic : Jurnal Ilmiah Psikologi, 2023)
This study aims to determine the effect of social media cancellation or cyber-ostracism on the mental condition of Instagram users based on the temporal need-threat model, as well as to assess the potential role of trait mindfulness in managing its negative effects. University student participants (M age = 21.248; SD = 1.21) were divided into cyber-ostracism scenario (n = 180) versus inclusion scenario (n = 179) groups and were required to complete the mood, four basic needs, and trait mindfulness scales. The results showed that cyber-ostracism had greater impact on the threat of the four basic needs compared to the mood of participants. Furthermore, trait mindfulness was found to predict lower threats to the needs of belonging, control, and meaningful existence, but not to self-esteem. The results also showed that the inclusion of trait mindfulness reduced the influence of cyber-ostracism on the fulfillment of control needs. These findings are expected to contribute to the understanding of the dynamics of cyber-ostracism and its emotional effects, as well as bridge the gap between the public phenomenon of cancel culture and ostracism literature.